Therapeutic communication laboratory: integrating mixed methods with digital tools and reflective professional practice - Molinero, Francisco; Jonsson, Gudberg K.; Anguera, M. Teresa; Hunyadi, Laszlo; Szekrényes, István (Frontiers in Psychology, 2025)
Communication has been recognized as the matrix in which the helping professionals operate in order to generate changes. In particular, psychotherapy is fundamentally a professional practice based, from its origins, on conversation. This study aims to establish the methodological and instrumental foundations of a therapeutic communication laboratory utilizing a mixed-methods approach. The primary objective is to develop and implement tools and procedures for the effective analysis of psychotherapy session recordings. We present a methodological proposal containing the foundations of a therapeutic communication laboratory which allows a new dialogue between professional practice and empirical research based on observation. We describe the processes of data incorporation and analysis of recorded sessions from a mixed methods perspective (Qual-Quan-Qual). The automation and integration of various digital tools, aligned with this mixed methods approach, are essential to achieve closer collaboration between practitioners and researchers. The incorporation of the transcription and labeling processes of the recordings into analysis tools such as Elan and Theme allows us to advance in these objectives. This approach enhances the training and supervision of psychotherapy professionals and bridges the gap between theoretical intervention models and their practical application. From a research standpoint, it enables the development of a knowledge base and observational instruments to advance the creation of more effective intervention models.